INCREASING THE VALUE OF BALINESE TEXTILES THROUGH AESTHETIC STORES DISPLAY - Darmastuti, Putu Ari; Diantari, Ni Kadek Yuni (Yayasan Sinergi Widya Nusantara, 2024)
Purpose: Providing education to Balinese traditional textile MSME business activists to be more sensitive in displaying and storing traditional Balinese textile works. Traditional textiles that have value and are the work of Balinese craftsmen would be a shame if they were not cared for and sold optimally. The high interest of consumers has made traditional Balinese textiles a commodity that continues to be sought after and will remain alive as long as Balinese traditions are maintained. Research methods: The creation method uses the Research-Based Design (RBD) method. This method was proposed by Teemu Leinonen, and inspired by design theories. Building design prototypes, emphasizing creative solutions, exploring ideas from various design concepts, continuous evaluation, and developing a design solution are the focus of this RBD methodology. Findings: Three traditional textiles that have high demand in the market, namely endek, songket and geringsing cloth, have different characteristics that influence how they are displayed. Endek cloth is a fairly light woven cloth made from cotton thread and has striking colors related to the display of traditional textiles such as lighting, humidity, and how to organize the placement of conventional cloth. Implications: Through this discussion, we hope it can have a positive impact on conventional textile MSME activists to further increase the selling value of traditional Balinese textiles.